Predictive Value of Pelvic MRI Combined with SCC-Ag on Lymphatic Metastasis in Cervical Cancer - JU Yuye; SU Rui; WANG Xiaohui (Zhongliu Fangzhi Yanjiu, 2022)
Objective To discuss the clinicopathological characteristics of cervical cancer patients with lymphatic metastasis, to evaluate lymph node metastasis in cervical cancer patients by combining pelvic MRI enlarged lymph nodes and SCC-Ag, and to analyze the prognostic value of the model. Methods We retrospectively analyzed the data of 124 patients with cervical cancer. The predictive model was established based on the result. Results The depth of interstitial infiltration, serum SCC-Ag change value before and after treatment, lymph node enlargement showed by pelvic MRI, D2-40 and Ki67 were independent risk factors for lymph node metastasis of cervical cancer (P < 0.05). The prediction model of lymph node metastasis: L=the serum SCC-Ag change value+7.127×lymph node enlargement showed by pelvic MRI+5.386×D2-40+5.135×the depth of interstitial infiltration+19.457×Ki67; the sensitivity was 78.6% and specificity was 79.2%. Conclusion The cervical cancer patients with L≥20.8261 should be noticed. Doctors should give them individualized neoadjuvant treatment, and ensure adequate surgical scope. The above lymphatic prediction model has predictive value for preoperative lymph node metastasis.